Patients related factors influencing the clients’ satisfaction on maternal healthcare services: a case of Rongai Sub-County Health Institutions of Nakuru County, Kenya - Tirop, Wendy Jemeli; Esilaba, Moses; Donde, Oscar O. (International Journal Of Community Medicine And Public Health, 2020)
Background: Maternal health care (MHC) intervention and its quality is an important health service and its quality is an important concern in addressing the challenges of high maternal mortality experienced in many counties of Kenya. Objective of this study was to determine patients related factors that influence the satisfaction of clients receiving maternal healthcare in Rongai Sub-County health institutions of Nakuru County, Kenya. Methods: The study adopted descriptive cross-sectional design with simple random sampling where the health care facilities were clustered according to administrative locations, the wards and the respective levels of care; hospitals, health centres and dispensaries. Simple random sampling was used to select the facilities for the study. Convenience sampling was applied to get 465 mothers and purposive sampling method used to get healthcare practitioners in charge of the selected healthcare facilities. A questionnaire was administered to women seeking maternal health care services in the facilities within Rongai Sub County to determine the clients’ satisfaction. Results: The finding of the study indicates that education level, employment status, level of income and distance from the healthcare facilities had significant influence on client satisfaction to maternal health services (p=0.040, 0.006, 0.0.023 and 0.031 respectively). Conclusions: The study recommends the need to organize community outreach to sensitize the community on issues pertaining to maternal healthcare. Additionally, there is need for adequate education and economic empowerment within Rongai Sub-county for proper provision and adoption of MHC Services.